2016
DOI: 10.1093/mmy/myw061
|View full text |Cite
|
Sign up to set email alerts
|

Mycological profile of tinea capitis in schoolchildren in rural southern Ethiopia

Abstract: Tinea capitis is a known common infection among schoolchildren in developing countries that is still underreported in Ethiopia. The aim of this study was to examine the epidemiologic and etiologic profile of tinea capitis among school-aged children in a rural area in southern Ethiopia. We collected demographic and clinicodermatological data from school children aged 3-12 years with tinea infections. Pathologic specimens were taken for potassium hydroxide (KOH) mount and mycological culture. Dermatophyte specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
2
11
2
Order By: Relevance
“…The variations could be associated with personal hygiene, poverty, and climate conditions [ 55 ], as well as immune factors [ 67 69 ]. Consistent with findings elsewhere in Ethiopia [ 22 , 29 , 70 ] and other African studies [ 65 , 71 73 ], boys were more likely to be affected by tinea infection (particularly tinea capitis) than girls, perhaps due to the higher risk associated with frequent shaving or haircuts [ 55 ] or due to personal hygiene (e.g., frequency of hair washing).…”
Section: Discussionsupporting
confidence: 86%
“…The variations could be associated with personal hygiene, poverty, and climate conditions [ 55 ], as well as immune factors [ 67 69 ]. Consistent with findings elsewhere in Ethiopia [ 22 , 29 , 70 ] and other African studies [ 65 , 71 73 ], boys were more likely to be affected by tinea infection (particularly tinea capitis) than girls, perhaps due to the higher risk associated with frequent shaving or haircuts [ 55 ] or due to personal hygiene (e.g., frequency of hair washing).…”
Section: Discussionsupporting
confidence: 86%
“…T. violaceum followed by M. canis was repeatedly reported to be the main causative organism of tinea capitis in Egypt and other North African countries 5,26,27 . Various other causative organisms had been reported from different parts of Africa including T. verrucosum , T. tonsurans , T. soudanense , and M. canis 4,28‐31 . In the United States, T. tonsurans is the most commonly isolated organism from tinea capitis patients replacing M. audouinii and M. canis 3,32‐34 .…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies performed in Iran, Didehdar [6], Abastabar [7], and Mohammadi [8] reported T. tonsurans, T. interdigitale, and M. canis as the most common frequent dermatophytes in TC, respectively. In a study carried out in a rural region in southern Ethiopia among schoolchildren, T. verrucosum was the most common pathogen of TC [21]. Identification of dominant pathogens of TC in each area is a matter of paramount importance in the selection of the proper treatment.…”
Section: Discussionmentioning
confidence: 99%